SU(3) mixing for excited mesons - Carvalho, W. S.; de Castro, A. S.; Antunes, ACB (Iop Publishing Ltd, 2002)
The SU(3)-flavour symmetry breaking and the quark-antiquark annihilation mechanism are taken into account for describing the singlet-octet mixing for several nonets assigned by the Particle Data Group (PDG). This task is approached with the mass matrix formalism.